The Influence of Sales Promotion and Trust on the Decision to Use ShopeePay Digital Wallet on the Shopee Application: A Case Study of Business Faculty Students at Mitra Indonesia University - Asrofi, Hendri; Meidasari, Evi; Silvia, Dewi (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to determine the Influence of Sales Promotion and Trust on the Decision to Use the Shopeepay Digital Wallet on the Shopee Application. The data used in this study are primary data obtained directly from the source, namely through respondents who filled out the questionnaire and secondary data are previous research, as well as theories and views from several experts that are relevant to the research theme. The analysis technique used is validity, reliability, classical assumptions, hypotheses and multiple linear regression. Based on the results of the analysis, it can be concluded that simultaneously the influence of sales promotion and trust has a significant effect on the decision to use the Shopeepay digital wallet on the Shopee application. Partially, the sales promotion variable has a negative effect on the decision to use and the trust variable has a positive effect on the decision to use. Thus, to increase the decision to use the Shopeepay digital wallet on the Shopee application, sales promotion and trust must be considered